Predictors of abnormal electrocardiograms in the pediatric emergency department - Shiv Gandhi; Miranda Lin; Sharon R Smith; Jesse J Sturm (Wolters Kluwer Medknow Publications, 2018)
Background: Electrocardiograms (ECGs) are ordered in the pediatric emergency room for a wide variety of chief complaints. Objectives: Criteria are lacking as to when physicians should obtain ECGs. This study uses a large retrospective cohort of 880 pediatric emergency department (ED) patients to highlight objective criteria including significant medical history and specific vital sign abnormalities to guide clinicians as to which patients might have an abnormal ECG. Methods: Retrospective review of Pediatric ED charts in all patients aged < 18 years who had ECG performed during ED stay. Pediatric ED physician interpretation of the ECG, clinical data on vital signs and past medical history was collected from the medical record for analysis. Results: Of 880 ECGs performed in the ED, 17.4% were abnormal. When controlled for medical history and demographic differences, abnormal ECGs were associated with age-adjusted abnormal ED vital signs including increased heart rate (odds ratio [OR] 1.85, 95% confidence interval [CI] 1.1-3.09) and increased respiratory rate (OR 1.74, CI 1.42-2.62). In a logistic regression analysis, certain chief complaints and history components were less likely to have abnormal ECGs including complaints of chest pain (OR 0.38, CI 0.18-0.80) and known history of gastrointestinal or respiratory condition (i.e., asthma) (OR 0.48, CI 0.29-0.79). Conclusions: In this cohort of patients, those with a chief complaint of chest pain or known respiratory conditions and normal age-adjusted vital signs in the ED have low likelihood of an abnormal ECG.